2020
DOI: 10.1039/d0qi00101e
|View full text |Cite
|
Sign up to set email alerts
|

A concerted evolution of supramolecular interactions in a {cation; metal complex; π-acid; solvent} anion-π system

Abstract: Comprehensive studies on a concerted evolution of supramolecular interactions with multicomponent synthon reproduction provide a new tool to describe the trapping of flat [M(L)4]2− complexes within π-acidic cavities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…The molecular environment of the tectons engaged in the hydrogen-bond networks is completed by the oligomeric arrays of PPh 4 + cations accompanied by some MeCN molecules; these components form multiple weak C-H•••A interactions (A = O atoms and ring system of H 3 PG, N atoms of [M(CN) 6 ] 3− ) in the regions not involved in the typical hydrogen bonds (Figure S3). The {PPh 4 + } ∞ 3D subnetwork itself provides substantial structural stabilization through so-called multiple phenyl embrace (MPE) motifs, here realized mainly by the sextuple phenyl embrace (SPE) or offset sextuple phenyl embrace (OSPE) and other hybrid patterns, with the shortest P•••P distances of 6.2, 6.6, and 7.3 Å in all structures [51,52] (Figure S4).…”
Section: Structural Studiesmentioning
confidence: 99%
“…The molecular environment of the tectons engaged in the hydrogen-bond networks is completed by the oligomeric arrays of PPh 4 + cations accompanied by some MeCN molecules; these components form multiple weak C-H•••A interactions (A = O atoms and ring system of H 3 PG, N atoms of [M(CN) 6 ] 3− ) in the regions not involved in the typical hydrogen bonds (Figure S3). The {PPh 4 + } ∞ 3D subnetwork itself provides substantial structural stabilization through so-called multiple phenyl embrace (MPE) motifs, here realized mainly by the sextuple phenyl embrace (SPE) or offset sextuple phenyl embrace (OSPE) and other hybrid patterns, with the shortest P•••P distances of 6.2, 6.6, and 7.3 Å in all structures [51,52] (Figure S4).…”
Section: Structural Studiesmentioning
confidence: 99%
“…The above observations are also in line with results presented in previous studies where structural analyses and detailed computational analyses of simple anion-π systems revealed that parallel anion orientations are preferred due to overlapping orbitals and their contribution to overall stabilization. 20,21,[70][71][72] Nevertheless, atypical angle distributions are observed in region A for such ions as citric acid, where no orientation is privileged, and the carboxylic group of heme strongly prefers edgewise geometry.…”
Section: Anion-ring Pair In Sequence -Secondary Structure Correlationsmentioning
confidence: 99%
“…Thus, canonical anion-π synthons reveal their significance in performance of advanced small-molecule catalytic systems dedicated to specific organic reactions, [1][2][3] photophysical systems based on charge or electron transfer properties, [4][5][6][7][8][9] anion recognition, binding, and sensing, [10][11][12][13] anion transport, [14][15][16][17] or anion directed self-assembly of polynuclear coordination complexes. 18 Further on, the new generation supramolecular and coordination anion-π architectures hosting mononuclear 8,[19][20][21] and polynuclear d-metalate complexes 9,22,23 were recently reported in the context of anion binding, 19,20 molecular crystalline composites, 21 charge transfer and photophysical properties, 8,9,[20][21][22] or magnetic properties. 23 In parallel, edgewise cooperative synthons that exploit multiple side ringC-Hanion contacts at the ring edge are well known to stabilise numerous molecular architectures.…”
Section: Introductionmentioning
confidence: 99%
“…The molecules in Chart are strong electron acceptors with reduction potentials of −0.20, 0.02, and 0.56 V vs SCE for TCP, FA, and DDQ, respectively. , The literature data indicated the propensity of these neutral π-acceptors to binding (pseudo)-halides, metal halides, and other anions. ,,,, In particular, the study of complexes of TCP with halide (Cl – , Br – , and I – ) anions provided evidence of anion−π bonding in solution and the solid state . The Mulliken dependence of the energy of the absorption bands, which was observed for the complexes of TCP and p -benzoquinones with (pseudo-)­halides suggested the charge transfer nature of such associations. , In the systems in which the strongest π-acceptors (e.g., DDQ) were combined with the I – or Br – anions (which are rather strong electron donors), the formation of the charge-transfer complexes was followed by electron transfer …”
Section: Introductionmentioning
confidence: 98%
“…20,32 The literature data indicated the propensity of these neutral π-acceptors to binding (pseudo)-halides, metal halides, and other anions. 18,20,21,33,34 In particular, the study of complexes of TCP with halide (Cl − , Br − , and I − ) anions provided evidence of anion−π bonding in solution and the solid state. 18 The Mulliken dependence of the energy of the absorption bands, which was observed for the complexes of TCP and pbenzoquinones with (pseudo-)halides suggested the charge transfer nature of such associations.…”
Section: Introductionmentioning
confidence: 99%